2013
DOI: 10.1186/1471-2229-13-167
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based protein profiling provides insights into the central metabolism changes driving grape berry development and ripening

Abstract: BackgroundGrapevine (Vitis vinifera L.) is an economically important fruit crop. Quality-determining grape components such as sugars, acids, flavors, anthocyanins, tannins, etc., accumulate in the different grape berry development stages. Thus, correlating the proteomic profiles with the biochemical and physiological changes occurring in grape is of paramount importance to advance in our understanding of berry development and ripening processes.ResultsWe report the developmental analysis of Vitis vinifera cv. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 107 publications
3
42
3
Order By: Relevance
“…While two proteins from the mevalonate pathway destined to the terpenoid backbone formation (isopentenyl diphosphate isomerase and 4‐hydroxy‐3‐methylbut‐2‐enyl diphosphate) were quantified, the downstream acting enzymes responsible for the synthesis of monoterpenes were barely detected. The same phenomenon is also observed in other biochemical pathways of the SM responsible for the biosynthesis of other important metabolites from a wine quality perspective such as the polyphenols, non‐flavonoids hydroxycinnamic acids (CAD), and the flavonoids anthocyanin (ANR, ANS) and proanthocyanidins (CHS, CHI, F3H) . The most frequently identified proteins (shown within brackets) belong to the early or mid‐pathway and the common central pathway of the phenylpropanoids (PAL).…”
supporting
confidence: 59%
See 2 more Smart Citations
“…While two proteins from the mevalonate pathway destined to the terpenoid backbone formation (isopentenyl diphosphate isomerase and 4‐hydroxy‐3‐methylbut‐2‐enyl diphosphate) were quantified, the downstream acting enzymes responsible for the synthesis of monoterpenes were barely detected. The same phenomenon is also observed in other biochemical pathways of the SM responsible for the biosynthesis of other important metabolites from a wine quality perspective such as the polyphenols, non‐flavonoids hydroxycinnamic acids (CAD), and the flavonoids anthocyanin (ANR, ANS) and proanthocyanidins (CHS, CHI, F3H) . The most frequently identified proteins (shown within brackets) belong to the early or mid‐pathway and the common central pathway of the phenylpropanoids (PAL).…”
supporting
confidence: 59%
“…The authors reported on proteins involved in the production of monoterpenes, volatile fatty acid derivatives, phenylpropanoids, benzenoid volatiles, and methoxypyrazines. Few proteomic studies have shown protein profiles regarding proteins involved in the production of aroma and flavor, [3] either because these proteins were not identified, or it was not in the scope of the investigation. To date there are only two publications that have focused entirely on the study of the profiles of proteins in ripening involved in the production of aroma and flavor volatiles in the grapes of two different varieties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Isobaric tags for relative and absolute quantification (iTRAQ) is a robust mass spectrometry of protein quantitative technology, which can perform relative and absolute quantification in up to eight samples in parallel (Bindschedler and Cramer, 2011; Glibert et al, 2014). Recently, iTRAQ has been widely used for large-scale quantitative plant proteomic studies in exploration of various metabolic processes at the post-transcriptional level (Kambiranda et al, 2013; Martínez-Esteso et al, 2013) in response to various stresses (Yang et al, 2014; Li et al, 2015; Fu et al, 2016). Additionally, iTRAQ-based proteomics has been proven as a powerful method for unraveling the molecular regulatory networks involved in interactions between heavy metals and plant species, and a set of HM-responsive candidate proteins have been successfully identified.…”
Section: Introductionmentioning
confidence: 99%
“…Today, it is cultivated in all temperate regions of the world. Considered as the most important fruit crop in the world, it plays an important role in the economy of many developed and emerging countries (Martínez-Esteso et al, 2013). Merlot is one of the most important grape cultivars in the wine industry.…”
Section: Introductionmentioning
confidence: 99%